Serum progesterone concentration on the day of embryo transfer in stimulated cycles does not correlate with reproductive outcomes. Issue 6 (December 2022) - Rozen, Genia; Rogers, Peter; Mizrachi, Yossi; Teh, Wan Tinn; Parmar, Chandrika; Polyakov, Alex
Abstract: Research question: Is the live birth rate (LBR) in fresh embryo transfer IVF cycles affected by serum progesterone concentration on the day of embryo transfer? Design: A single-centre retrospective analysis of prospectively collected data from women who underwent IVF or intracytoplasmic sperm injection between July 2019 and July 2020, and had a fresh day 5 single embryo transfer. Overall, 825 first and second stimulation cycles were included. Patients underwent a gonadotrophin-releasing hormone antagonist protocol with human chorionic gonadotrophin (HCG) trigger, and received vaginal-only luteal phase support. The study population was an everyday patient cohort, treated with the unit's usual stimulation protocols. The correlation between serum progesterone concentrations on the day of embryo transfer and the incidence of positive HCG, clinical pregnancy and live birth were examined. Patients were divided into four groups based on serum progesterone concentrations (<150, 150–250, 251–400 and >400 nmol/l). The data were further interrogated using additional progesterone cut-offs. Results: There was no concentration of progesterone below or above which the chance of pregnancy was reduced. The chance of live birth following a blastocyst transfer was no different across the four groups (29.8, 26.6, 32.7 and 31.5%, respectively, P = 0.55). There was no negative association between progesterone and chance of pregnancy when other progesterone thresholds were applied. Estimates were adjusted for confounding factors such as maternal age. Conclusion: Serum progesterone concentration on the day of fresh embryo transfer does not correlate with the LBR.